2023
DOI: 10.1002/iub.2773
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of nuclear export and import receptors in cancer and their potential in combination chemotherapy

Stella Newell,
Pauline J. van der Watt,
Virna D. Leaner

Abstract: Systemic modalities are crucial in the management of disseminated malignancies and liquid tumours. However, patient responses and tolerability to treatment are generally poor and those that enter remission often return with refractory disease. Combination therapies provide a methodology to overcome chemoresistance mechanisms and address dose‐limiting toxicities. A deeper understanding of tumorigenic processes at the molecular level has brought a targeted therapy approach to the forefront of cancer research, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 217 publications
0
2
0
Order By: Relevance
“…[73] Recently, tumorigenesis was associated with the dysregulation of cellular import, export or bidirectional transport receptors by changes in their expression or subcellular localization, [74] which provoke the nuclear retention of tumor suppressors and key mediators of oncogenic signaling. [75] Thus, nuclear transport inhibition (e.g., exportin 1 (EXPO1) by selinexor) combined with the anticancer drug dexamethasone, abolish oncogenic signaling and restore the activity of tumor suppressor functions, a combination therapy that may overcome chemoresistance and focus on dose-limiting toxicities. [75] Several preclinical studies have reported many combination agents for colon cancer prevention using different mice and rat models that moved into clinical trials.…”
Section: Combined Protocols Centered In Dha Plus Epamentioning
confidence: 99%
See 1 more Smart Citation
“…[73] Recently, tumorigenesis was associated with the dysregulation of cellular import, export or bidirectional transport receptors by changes in their expression or subcellular localization, [74] which provoke the nuclear retention of tumor suppressors and key mediators of oncogenic signaling. [75] Thus, nuclear transport inhibition (e.g., exportin 1 (EXPO1) by selinexor) combined with the anticancer drug dexamethasone, abolish oncogenic signaling and restore the activity of tumor suppressor functions, a combination therapy that may overcome chemoresistance and focus on dose-limiting toxicities. [75] Several preclinical studies have reported many combination agents for colon cancer prevention using different mice and rat models that moved into clinical trials.…”
Section: Combined Protocols Centered In Dha Plus Epamentioning
confidence: 99%
“…[75] Thus, nuclear transport inhibition (e.g., exportin 1 (EXPO1) by selinexor) combined with the anticancer drug dexamethasone, abolish oncogenic signaling and restore the activity of tumor suppressor functions, a combination therapy that may overcome chemoresistance and focus on dose-limiting toxicities. [75] Several preclinical studies have reported many combination agents for colon cancer prevention using different mice and rat models that moved into clinical trials. [76] These comprise the assessment of the prevalence of T2DM in patients with colorectal adenocarcinoma (CRC) and survival for CRC in patients defined by CRC stage, presence or absence of T2DM treated with metformin, and presence or absence of daily aspirin therapy.…”
Section: Combined Protocols Centered In Dha Plus Epamentioning
confidence: 99%